Pocket Guide to Crime Scene Photography - Vecellio, Mark E.; Bryant, Erick P. (Boca Raton, FL : CRC Press, 2017)
"This handy pocket guide is an essential field guide to crime scene photography. The authors have used limited technical terms and jargon to distill concepts down to understandable, step-by-step methodologies. The book highlights best practices that apply to most any crime scene but specialized instructions$1 (Bpertaining to unique evidence and crime scenes that present challenging conditions$1 (Bare also provided. The book introduces concise, comprehensive checklists for photographing such evidence as tire tracks, dust impressions, fingerprints, luminescence from trace blood search reagents, and more. This convenient reference allows police professionals, investigators, and crime scene analysts and technicians to improve their proficiency to achieve professional, reliable results."--Provided by publisher.s
chapter 1 Providing Context -- chapter 2 Equipment and Accessories -- chapter 3 Camera Terms and Photography Principles Made Easy to Understand -- chapter 4 Crime Scene Photography: An Overview and Checklist -- chapter 5 Overall Photographs -- chapter 6 Mid-Range Photographs -- chapter 7 Close-Up Photographs -- chapter 8 Photographing Footwear/Tire Tracks and Impressions -- chapter 9 Photographing Latent Fingerprints -- chapter 10 Night Photography, Painting with Light, / Long-Shutter Duration Photography -- chapter 11 Alternate Light Source Photography -- chapter 12 Photographing Vehicles -- chapter 13 Injury/Deceased Remains Photography.
Keywords: Crime scene searches; Legal photography; Criminology and Criminal Justice; Forensic Science; LAW / Forensic Science